Endotoxicosis as the Contents of Posresuscitative Disease in Acute Poisoning - Ye. A. Luzhnikov; Yu. S. Goldfarb; K. K. Ilyashenko (Общая реаниматология)
Objective: to study the specific features of the diagnosis and treatment of endothoxicosis as a manifestation of postresus-citative disease in acute exogenous poisoning.Subjects and methods. Clinical, laboratory, and statistical methods of the diagnosis of endotoxicosis complicating the course of acute poisoning by narcotics, psychopharmacological agents, and cauterants, as well as complex physicochemical detoxification were applied to 554 patients.Results. The study pathology has been ascertained to have 3 developmental stages — from functional (primary) to developed and terminal clinical and laboratory manifestations as multiple organ dysfunctions. The best therapeutic results are achieved by effective therapeutic measures just in early-stage endotoxicosis, by substantially reducing the rates of death and pneumonia and the time of the latter’s resolution. The major contribution to the reduction in the rate of death due acute poisoning is associated with physicochemical detoxification that considerably lessens the influence of the intoxication factors of postresuscitative disease.Conclusion. When diagnosing endotoxicosis in patients with acute endogenous intoxication, it is necessary to keep in mind a whole spectrum of typical changes in endotoxicosis markers and homeostatic parameters: hematologi-cal, blood rheological, lipid peroxidation/antioxidative systems, which should be timely corrected by the basic efferent artificial detoxification techniques (hemosorption, hemodiafiltration, hemofiltration), by compulsorily employing physio-and chemohemotherapy (laser-ultraviolet hemotherapy, sodium hypochlorite infusion).